Management of Bilateral Wilms’ Tumor: Our Experience - Raghunath BV (Indian J Surg Oncol, 2016)
Management of bilateral Wilms’ tumor is particularly challenging, considering the chances of recurrence and long-term renal function for affected patients. Aggressive surgical resection to prevent recurrence must be balanced with the desire to preserve renal function. We evaluated our experience in the management of bilateral Wilms’ tumor stressing the challenges encountered in decision making and the role of nephron sparing surgery. We had four children presenting with bilateral Wilms’ tumor. All of them were appropriately staged and given standard chemotherapy as per NWTS-5 guidelines. Tumors were considered to have a ‘good’ response to chemotherapy if sufficient tumor shrinkage was observed so that renal hilum was seen free of tumor and vice versa. Nephron-sparing surgery was considered in all and was performed when feasible, followed by completion adjuvant chemotherapy. All patients were followed up with serial ultrasound scans (3–6 monthly) and CECT abdomen (yearly once). Blood urea and serum creatinine, hypertension, and proteinuria were assessed during follow-up visits. All four children received neo-adjuvant chemotherapy as per NWTS-5 guidelines. The first child had poor response to chemotherapy and was considered for left radical and right partial nephrectomy. However, patient attenders refused any surgical intervention and the child was taken home. The second child had a ‘good’ response on left side and was planned for left partial and right radical nephroureterectomy based on pre-operative imaging analysis. However, intra-operatively, bilateral partial nephrectomy with good margins was feasible. The third child though, showed ‘poor’ response to pre-op chemotherapy and warranted bilateral nephroureterectomy, right partial and left radical nephroureterectomy was feasible. However, in the fourth child, we were not able to perform nephron sparing surgery and left nephroureterectomy with right tumor biopsy was done. Following this, child was started on 2nd-line chemotherapy, now awaiting right partial nephrectomy. The second child is on follow up for 1.5 years, doing well. However, the third child expired 1.5 years following surgery due to recurrence (lung metastasis). Management of bilateral Wilm’s tumor is challenging and nephron-sparing surgery should be considered in all patients having bilateral Wilm’s tumor with favorable histology, even if pre-operative imaging studies suggest that the lesions are unresectable.